Wernicke's area revisited: parallel streams and word processing. - DeWitt, Iain; Rauschecker, Josef P (Brain & Language, 2013)
Auditory word-form recognition was originally proposed by Wernicke to occur within left superior temporal gyrus (STG), later further specified to be in posterior STG. To account for clinical observations (specifically paraphasia), Wernicke proposed his sensory speech center was also essential for correcting output from frontal speech-motor regions. Recent work, in contrast, has established a role for anterior STG, part of the auditory ventral stream, in the recognition of species-specific vocalizations in nonhuman primates and word-form recognition in humans. Recent work also suggests monitoring self-produced speech and motor control are associated with posterior STG, part of the auditory dorsal stream. Working without quantitative methods or evidence of sensory cortex' hierarchical organization, Wernicke co-localized functions that today appear dissociable. "Wernicke's area" thus may be better construed as two cortical modules, an auditory word-form area (AWFA) in the auditory ventral stream and an "inner speech area" in the auditory dorsal stream.